Penerapan Algoritma C4.5 untuk Klasifikasi Data Rekam Medis berdasarkan International Classification Diseases (ICD-10) - Yudha Aditya Fiandra; Sarjon Defit; Yuhandri Yuhandri (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2017)
Abstract The medical record data is the patient's current record of medical records, the medical record data only being data stacked and not traced to generate useful knowledge for the hospital. This study can process the medical record data to classify the disease that occurs in sleeping sickness based on ICD-10. The method used in this research is C4.5 algorithm method by using attribute of international disease code as attribute of destination label as many as 21 international disease group, that is: A00-B99 up to Z00-Z99. This study yields a decision of the value code, C4.5 code can represent as many as 14 attribute values ​​of disease code objectives and data percentage that read more than 66%. The conclusion of this research is C4.5 algorithm help classify international disease code based on ICD-10 and decision tree making which can give information of any disease that often happened at hospital Keywords: data mining, classification, C4.5, medical records, ICD-10